DIFFERENT TECTONO-THERMAL EVOLUTIONARY PATHS IN ECLOGITIC ROCKS FROM THE AXIAL ZONE OF THE VARISCAN CHAIN IN SARDINIA (ITALY) COMPARED WITH THE LIGURIAN ALPS - Cortesogno, Luciano; Gaggero, Laura; Oggiano, Giacomo; Paquette, Jean-Louis (Ofioliti, 2004)
The inner zone of the Sardinia Variscan segment consists of two metamorphic complexes: I) A polymetamorphic Migmatite Complex, with migmatites showing polyphase anatectic processes, in the presence of kyanite or sillimanite. The Migmatite complex preserved decametric lenses of eclogite relicts (eclogites A) affected by high T, high- to intermediate P recrystallization under granulite facies conditions The decompressional garnet + Ca-clinopyroxene + amphibole ± orthopyroxene-bearing assemblages developed in granoblastic textures generally in no stress conditions. In most cases, only symplectite textures provide evidence for the eclogitic event. II) A medium grade, mostly metapelitic complex consisting of Grt, Ky, Stau-bearing micaschists and paragneisses includes quartzites and garnet-bearing amphibolite boudins with N-MORB chemical affinity. Relicts of eclogite assemblages were locally found in the metabasite (eclogites B). In eclogites A, the geothermobarometric parameters yield temperatures in the range 690°-760°C for minimum pressure Å1.3 GPa. Pyroxene compositions accord with temperatures in excess of 700°C. In eclogites B, the thermometric calibrations provide temperatures in the range 610°-700°C for pressures 1.3-1.5 GPa, based on the jadeite content. The temperatures are consistent with the biotite+muscovite+garnet+kyanite+staurolite assemblage in the host paragneisses, and with lack of anatectic processes. The age of 457±2 Ma, obtained by U/Pb dating on one sample of Type A eclogite is interpreted as a minimum estimate for the magmatism of the eclogite protolith. A second zircon population defined an age of 403±4 Ma interpreted as dating the zircon crystallization during the high-grade event. The relationships between Types A and B eclogites, and their bearing on the regional framework (Sardinia, Ligurian Alps) are discussed.